2020
DOI: 10.48550/arxiv.2009.04784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

beta Cas: the first delta Scuti star with a dynamo magnetic field

K. Zwintz,
C. Neiner,
O. Kochukhov
et al.

Abstract: Context. F type stars are characterised by several physical processes such as different pulsation mechanisms, rotation, convection, diffusion, and magnetic fields. The rapidly rotating δ Scuti star β Cas can be considered as a benchmark star to study the interaction of several of these effects. Aims. We investigate the pulsational and magnetic field properties of β Cas. We also determine the star's apparent fundamental parameters and chemical abundances. Methods. Based on photometric time series obtained from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Just recently however, Zwintz et al (2020) showed that β Cas, an F2III δ Sct type pulsator with only three p-mode frequencies of low amplitude, has a complex magnetic field very possibly of dynamo origin. β Cas is a terminal-age mainsequence (TAMS) star with log g = 3.53±0.58 and T eff = 6920±140 K, rotating very fast with P rot = 0.898 d which probably helps to maintain the dynamo even at such high temperature (Zwintz et al 2020). Thus, KIC 5080290 could be another example of a pulsating star with magnetic activity.…”
Section: The Case Of Kic 5080290mentioning
confidence: 99%
“…Just recently however, Zwintz et al (2020) showed that β Cas, an F2III δ Sct type pulsator with only three p-mode frequencies of low amplitude, has a complex magnetic field very possibly of dynamo origin. β Cas is a terminal-age mainsequence (TAMS) star with log g = 3.53±0.58 and T eff = 6920±140 K, rotating very fast with P rot = 0.898 d which probably helps to maintain the dynamo even at such high temperature (Zwintz et al 2020). Thus, KIC 5080290 could be another example of a pulsating star with magnetic activity.…”
Section: The Case Of Kic 5080290mentioning
confidence: 99%